Air capacity for Sydney - Peter Forsyth (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Like most large cities, Sydney has an airport problem. Demand is increasing faster than supply, and additional capacity will be needed if costly rationing, and delays, are to be avoided. However, compared to many cities, the problems facing Sydney are modest. At the moment, demand is only just exceeding capacity. There is a good chance that the available capacity will be rationed efficiently. Options for expanding capacity are being evaluated well. There may be problems in the future- poor options may be chosen over good options.
Keywords: 330